A calamitic mesogenic near-infrared absorbing croconaine dye/liquid crystalline elastomer composite. Issue 7 (4th April 2016) - Guo, Ling-Xiang; Liu, Mei-Hua; Sayed, Sayed Mir; Lin, Bao-Ping; Keller, Patrick; Zhang, Xue-Qin; Sun, Ying; Yang, Hong
Abstract : The first example of a calamitic mesogenic NIR absorbing organic dyeYHD796 is reported. The corresponding homogeneously-aligned LCE/YHD796 composite film can perform a fully reversible NIR-stimulated contraction/expansion response. Abstract : In this work, we report the first example of a calamitic mesogenic near-infrared (NIR) absorbing organic dye, made by functionalizing a thiophene–croconaine chromophore rigid core with two symmetric long flexible alkyl chains. The liquid crystal (LC) NIR dyeYHD796 exhibits a sharp and intense NIR absorption band with a maximum absorption peak at 796 nm. Taking advantage of the improved solubility ofYHD796 dispersed in mesogenic molecules, a homogeneously-aligned mono-domain liquid crystalline elastomer (LCE)/YHD796 composite film is successfully prepared by applying the classical LC-cell-alignment method and in situ photo-polymerization of photocurable LC monomer mixtures. This LCE/YHD796 composite film performs a fully reversible contraction/expansion response towards NIR light stimulus due to the photo-thermal heating effect induced by theYHD796 dye well-dispersed in the LCE matrix.